Effect of Tribulus terrestris supplementation on the organism of rats fed a high-fat diet - Lieshchova, M. O.; Lieshchova, M. А.; Lieshchova, M.; Lieshchova, Maryna; Lieshchova, Marina; Leshchova, M. O.; Lieshova, M.; Лєщова, Марина Олексіївна; Brygadyrenko, V. V.; Бригадиренко, В. В. (Oles Honchar Dnipropetrovsk National University, 2025)
Recently, the global community has turned its attention to the use of antioxidant-rich herbs. Researchers have also looked i n to using them to develop natural antioxidant formulas in the fields of medicine and nutrition. In particular, they ha ve been studied for their potential to treat or correct metabolic disorders caused by an unbalanced diet. Tribulus terrestris is rich in secondary metabolites and is known for its antitumor, antilithic, antidiabetic, anti-inflammatory, and antioxidant properties. It has also been used for a long time to treat sexual dysfunction. In a laboratory study, 20 adult male rats were fed a high-fat diet supplemented with 0.5% or 2.0% dry T. terrestris herb for 32 days. The rats' weight gain, internal organ mass, and indicators of protein, lipid, carbohydrate, and mineral metabolism and blood enzyme activity were observed. The body weight of the animals that received a high-fat diet increased to 105.7% of the initial weight by the end of the experiment. The addition of T. terrestris herb to the diet at a dose of 0.5% did not affect the rate of body weight gain, while a dose of 2.0% contributed to an increase in body weight gain (up to 107.4%). Tribulus terrestris did not significantly alter feed intake or water consumption. A high-fat diet supplemented with T. terrestris caused a dose-dependent increase in liver weight; the 2.0% dose significantly increased the relative weight of the testicles and stomach. Both doses of the T. terrestris herb significantly reduced blood glucose levels. The 2.0% dose increased high-density lipoprotein (HDL) cholesterol and inorganic phosphorus levels while decreasing the Ca/P ratio. Depending on the dose, T. terrestris herb had a mixed effect on creatinine levels, causing either a decrease at 0.5% or an increase at 2.0%. AST and ALT activity was sharply increased by a 2.0% dose of T. terrestris herb. These results suggest the potential use of T. terrestris as a dietary supplement for correcting metabolic disorders in an unbalanced diet. Останнім часом світова спільнота звернула свою увагу на використання трав, багатих на антиоксиданти. Дослідники також розглядали їх використання для розробки натуральних антиоксидантних формул у сферах медицини та харчування. Tribulus terrestris багатий на вторинні метаболіти та відомий своїми протипухлинними, протилітичними, протидіабетичними, протизапальними та антиоксидантними властивостями. У лабораторному дослідженні 20 дорослих самців щурів протягом 32 днів годували дієтою з високим вмістом жирів, доповненою 0,5% або 2,0% сухої трави T. terrestris. Спостерігали за збільшенням ваги щурів, масою внутрішніх органів, а також показниками білкового, ліпідного, вуглеводного та мінерального обміну, а також активністю ферментів крові. Маса тіла тварин, які отримували дієту з високим вмістом жирів, до кінця експерименту збільшилася до 105,7% від початкової ваги. Додавання трави T. terrestris до раціону в дозі 0,5% не вплинуло на швидкість збільшення маси тіла, тоді як доза 2,0% сприяла збільшенню приросту маси тіла (до 107,4%). Раціон з високим вмістом жирів, доповнений T. terrestris, спричинив дозозалежне збільшення маси печінки; доза 2,0% значно збільшила відносну вагу яєчок та шлунка. Обидві дози трави T. terrestris значно знизили рівень глюкози в крові. Доза 2,0% підвищила рівень холестерину ліпопротеїнів високої щільності (ЛПВЩ) та рівень неорганічного фосфору, одночасно знижуючи співвідношення Ca/P. Залежно від дози, трава T. terrestris мала змішаний вплив на рівень креатиніну, викликаючи або зниження на 0,5%, або підвищення на 2,0%. Активність АСТ та АЛТ різко підвищилася при дозі 2,0% трави T. terrestris. Ці результати свідчать про потенційне використання T. terrestris як харчової добавки для корекції метаболічних порушень при незбалансованому харчуванні.
Вплив добавок Tribulus terrestris на організм щурів, яких годували раціоном з надлишком жирів
Лєщова Марина Олексіївна http://orcid.org/0000-0002-4251-4152
Keywords: obesity correction; корекція ожиріння; relative organ mass; відносна маса органів; increase in body weight; збільшення маси тіла; caltrop; кальтроп; high-fat diet; дієта з високим вмістом жирів; phytotherapy; фітотерапія